2000
DOI: 10.1139/z99-206
|View full text |Cite
|
Sign up to set email alerts
|

Winter survivorship of hatchling painted turtles (Chrysemys picta) in Michigan

Abstract: Hatchling painted turtles (Chrysemys picta) often exhibit delayed emergence by remaining in shallow sub- terranean nest cavities throughout winter. As a result, those at northern latitudes are sometimes exposed to lethal subzero temperatures. Our field study compared survivorship of hatchling C. picta during a winter in which low subzero temperatures coincided with the absence of insulating snow cover (1995-1996) with survivorship during the following three winters (1996-1997, 1997-1998, and 1998-1999), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…The greatest numbers of hatchlings emerged at air temperatures of~12°C or higher following~0.5 cm or more of rain, although five hatchlings emerged on days when air temperature fell below 5°C. Internal nest temperatures lag behind changes in ambient air temperature and the relationship between the two is influenced by factors such as terrain, ground temperature and cover, insolation, and time of day (Costanzo et al 1995;Nagle et al 2000;Doody et al 2001). Thus, following periods of warmer temperatures and soaking rains, a few hatchlings appeared to emerge shortly after cold fronts had moved in, entering into environments colder than their nests.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The greatest numbers of hatchlings emerged at air temperatures of~12°C or higher following~0.5 cm or more of rain, although five hatchlings emerged on days when air temperature fell below 5°C. Internal nest temperatures lag behind changes in ambient air temperature and the relationship between the two is influenced by factors such as terrain, ground temperature and cover, insolation, and time of day (Costanzo et al 1995;Nagle et al 2000;Doody et al 2001). Thus, following periods of warmer temperatures and soaking rains, a few hatchlings appeared to emerge shortly after cold fronts had moved in, entering into environments colder than their nests.…”
Section: Resultsmentioning
confidence: 99%
“…Since those early reports, however, additional field studies have indicated that partially developed embryos and unpipped eggs are unable to tolerate the rigors of winter in shallow, terrestrial nests (MacCulloch and Secoy 1983;Storey et al 1988;St. Clair and Gregory 1990;Lindeman 1991;Congdon et al 2000;Nagle et al 2000). Thus, turtle embryos at northern latitudes that fail to complete development before winter appear to inevitably die in their nests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, turtles that freeze in the laboratory under conditions like those they encounter in natural nests usually are supercooled by several degrees at the instant of nucleation and the experience is usually fatal Packard, 1993b, 1995;Packard et al, 1997bPackard et al, , 1999a. Moreover, temperatures in natural nests at northern localities generally go below -2°C for longer than 4·days, and they commonly go below the minimum tolerable temperature of -4°C at some point during the winter (Woolverton, 1963;DePari, 1996;Packard et al, 1997a;Weisrock and Janzen, 1999;Nagle et al, 2000;Costanzo et al, 2004). These considerations alone render it highly unlikely that hatchlings overwintering in the field typically survive until spring by withstanding the physiological challenges of freezing.…”
mentioning
confidence: 99%
“…Moreover, even when temperatures in nests are sufficiently benign that hatchlings could conceivably survive a short bout of freezing (e.g. Nagle et al, 2000;Costanzo et al, 2004), the turtles are unlikely to be frozen Packard, 1995, 2003a,b;Willard et al, 2000) for reasons detailed below.…”
mentioning
confidence: 99%